Role of CD8(+) T Cells and Lymphoid Dendritic Cells in Protection from Ocular Herpes Simplex Virus 1 Challenge in Immunized Mice - Matundan, Harry (American Society for Microbiology, 2014)
The development of immunization strategies to protect against ocular infection with herpes simplex virus 1 (HSV-1) must address the issue of the effects of the strategy on the establishment of latency in the trigeminal ganglia (TG). It is the reactivation of this latent virus that can cause recurrent disease and corneal scarring. CD8(+) T cells and dendritic cells (DCs) have been implicated in the establishment and maintenance of latency through several lines of inquiry. The objective of the current study was to use CD8α(−/−) and CD8β(−/−) mice to further evaluate the contributions of CD8(+) T cells and the CD8α(+) and CD8α(−) subpopulations of DCs to the protection afforded against ocular infection by immunization against HSV-1 and their potential to increase latency. Neutralizing antibody titers were similar in immunized CD8α(−/−), CD8β(−/−), and wild-type (WT) mice, as was virus replication in the eye. However, on day 3 postinfection (p.i.), the copy number of HSV-1 glycoprotein B (gB) was higher in the corneas and TG of CD8α(−/−) mice than those of WT mice, whereas on day 5 p.i. it was lower. As would be anticipated, the lack of CD8α(+) or CD8β(+) cells affected the levels of type I and type II interferon transcripts, but the effects were markedly time dependent and tissue specific. The levels of latent virus in the TG, as estimated by measurement of LAT transcripts and in vitro explant reactivation assays, were lower in the immunized, ocularly challenged CD8α(−/−) and WT mice than in their CD8β(−/−) counterparts. Immunization reduced the expression of PD-1, a marker of T-cell exhaustion, in the TG of ocularly challenged mice, and mock-immunized CD8α(−/−) mice had lower levels of PD-1 expression and latency than mock-immunized WT or CD8β(−/−) mice. The expansion of the CD8α(−) subpopulation of DCs through injection of WT mice with granulocyte-macrophage colony-stimulating factor (GM-CSF) DNA reduced the amount of latency and PD-1 expression in the TG of infected mice. In contrast, injection of FMS-like tyrosine kinase 3 ligand (Flt3L) DNA, which expanded both subpopulations, was less effective. Our results suggest that the absence of both CD8α(+) T cells and CD8α(+) DCs does not reduce vaccine efficacy, either directly or indirectly, in challenged mice and that administration of GM-CSF appears to play a beneficial role in reducing latency and T-cell exhaustion. IMPORTANCE In the past 2 decades, two large clinical HSV vaccine trials were performed, but both vaccine studies failed to reach their goals. Thus, as an alternative to conventional vaccine studies, we have used a different strategy to manipulate the host immune responses in an effort to induce greater protection against HSV infection. In lieu of the pleiotropic effect of CD8α(+) DCs in HSV-1 latency, in this report, we show that the absence of CD8α(+) T cells and CD8α(+) DCs has no adverse effect on vaccine efficacy. In line with our hypothesis, we found that pushing DC subpopulations from CD8α(+) DCs toward CD8α(−) DCs by injection of GM-CSF reduced the amount of latent virus and T-cell exhaustion in TG. While these studies point to the lack of a role for CD8α(+) T cells in vaccine efficacy, they in turn point to a role for GM-CSF in reducing HSV-1 latency.